2008
DOI: 10.1038/ismej.2008.120
|View full text |Cite
|
Sign up to set email alerts
|

Detection of inteins among diverse DNA polymerase genes of uncultivated members of the Phycodnaviridae

Abstract: Viruses in the family Phycodnaviridae infect autotrophic protists in aquatic environments. Application of a PCR assay targeting the DNA polymerase of viruses in this family has revealed that phycodnaviruses are quite diverse and appear to be widespread, but a limited number of environments have been examined so far. In this study, we examined the sequence diversity among viral DNA pol genes amplified by PCR from subtropical coastal waters of O'ahu, Hawai'i. A total of 18 novel prasinovirus-like sequences were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 41 publications
2
31
0
1
Order By: Relevance
“…polB identification and qPCR Phylogenetic analyses of AVS-amplified polB sequences from spring, summer and fall clone libraries revealed that, with the exception of a single sequence, they were all most closely related to cultivated prasinoviruses when compared with other phycodnaviruses. These results are consistent with those from previous studies demonstrating that all, or nearly all environmental sequences obtained with the AVS-1 and 2 primers cluster with polB genes from marine prasinoviruses (for example, Short and Suttle, 2002;Short and Short, 2008;Clasen and Suttle, 2009;Culley et al, 2009). It is known that these primers do not amplify polB genes from other phycodnaviruses, such as Emiliania huxleyi virus, Heterosigma akashiwo virus, Chrysochromulina ericina virus and Pyramimonas orientalis virus, for example, Larsen et al, 2008).…”
Section: Resultssupporting
confidence: 82%
“…polB identification and qPCR Phylogenetic analyses of AVS-amplified polB sequences from spring, summer and fall clone libraries revealed that, with the exception of a single sequence, they were all most closely related to cultivated prasinoviruses when compared with other phycodnaviruses. These results are consistent with those from previous studies demonstrating that all, or nearly all environmental sequences obtained with the AVS-1 and 2 primers cluster with polB genes from marine prasinoviruses (for example, Short and Suttle, 2002;Short and Short, 2008;Clasen and Suttle, 2009;Culley et al, 2009). It is known that these primers do not amplify polB genes from other phycodnaviruses, such as Emiliania huxleyi virus, Heterosigma akashiwo virus, Chrysochromulina ericina virus and Pyramimonas orientalis virus, for example, Larsen et al, 2008).…”
Section: Resultssupporting
confidence: 82%
“…employed under nonoptimal conditions. No inteins were identified in these viral genomes, although inteins with homing endonucleases have been observed in prasinoviruses (62), including some Ostreococcus viruses (63), and in some green algae, including Bathycoccus, with viruses being a proposed mechanism for propagation (64).…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al 1996, Short & Suttle 2002, Short & Short 2008, Clasen & Suttle 2009, Culley et al 2009, and by demonstrating the existence of polB fragments from unknown types of phycodnaviruses. Amplification with degenerate Chlorovirus-specific primers led to the recovery of Lake Ontario sequences that represent a new type of Chlorovirus.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the algal virusspecific polB primers AVS1 and AVS2 have been used to amplify genes from different types of chloroviruses, prasinoviruses and prymnesioviruses (Chen & Suttle 1995, Brussaard et al 2004, Bellec et al 2009). However, with the exception of 1 operational taxonomic unit (OTU, or a DNA sequence ≤97% identical to any other) from the Gulf of Mexico (Chen et al 1996), and 2 from Kane'ohe Bay, O'ahu, Hawai'i, USA (Culley et al 2009), polB fragments amplified from natural environments using the AVS primers have all been most closely related to cultivated marine prasinoviruses (Short & Short 2008, Clasen & Suttle 2009, Culley et al 2009). …”
Section: Introductionmentioning
confidence: 99%